Inhibition of AZIN2-sv induces neovascularization and improves prognosis after myocardial infarction by blocking ubiquitin-dependent talin1 degradation and activating the Akt pathwayResearch in context - Xinzhong Li; Yili Sun; Senlin Huang; Yanmei Chen; Xiaoqiang Chen; Mengsha Li; Xiaoyun Si; Xiang He; Hao Zheng; Lintao Zhong; Yang Yang; Wangjun Liao; et al. (EBioMedicine, 2019)
Background: We previously found that loss of lncRNA-AZIN2 splice variant (AZIN2-sv) increases cardiomyocyte (CM) proliferation and attenuates adverse ventricular remodelling post-myocardial infarction (MI). However, whether inhibition of AZIN2-sv can simultaneously induce angiogenesis and thus improve prognosis after MI is unclear. Methods: We used in situ hybridization and quantitative PCR to determine AZIN2-sv expression in endothelial cells. Knockdown and overexpression were performed to detect the role of AZIN2-sv in endothelial cell function, angiogenesis and prognosis after MI. RNA pulldown, RNA immunoprecipitation and luciferase reporter assays were used to determine the interaction with talin1 (Tln1) protein and miRNA-214 (miR-214). DNA pulldown and chromatin immunoprecipitation (ChIP) assays were used to study AZIN2-sv binding to upstream transcription factors. Findings: AZIN2-sv was enriched in cardiac endothelial cells. The loss of AZIN2-sv reduced endothelial cell apoptosis and promoted endothelial sprouting and capillary network formation in vitro. Moreover, in vivo, the loss of AZIN2-sv induced angiogenesis and improved cardiac function after MI. Mechanistically, AZIN2-sv reduced Tln1 and integrin β1 (ITGB1) protein levels to inhibit neovascularization. AZIN2-sv activated the ubiquitination-dependent degradation of Tln1 mediated by proteasome 26S subunit ATPase 5 (PSMC5). In addition, AZIN2-sv could bind to miR-214 and suppress the phosphatase and tensin homologue (PTEN)/Akt pathway to inhibit angiogenesis. With regard to the upstream mechanism, Bach1, a negative regulator of angiogenesis, bound to the promoter of AZIN2-sv and increased its expression. Interpretation: Bach1-activated AZIN2-sv could participate in angiogenesis by promoting the PSMC5-mediated ubiquitination-dependent degradation of Tln1 and blocking the miR-214/PTEN/Akt pathway. Inhibition of AZIN2-sv induced angiogenesis and myocardial regeneration simultaneously, thus, AZIN2-sv could be an ideal therapeutic target for improving myocardial repair after MI. Fund: National Natural Science Foundations of China. Keywords: AZIN2-sv, Angiogenesis, Tln1, Ubiquitination